Citizenship Politics (Reviewing the Meaning of Democracy in Majanggut I Village, Royal District Pakpak Bharat Regency) - Budi Ali Mukmin; Suprayetno Suprayetno; Bakhrul Khair Amal; Nurhairani Nurhairani (Budapest International Research and Critics University, 2019)
Citizenship Politics in Majanggut I Village is the topic that will be discussed in this research. Maintaining the consolidation of democracy in the midst of the high level of cultural, religious and ethnic diversity is not an easy matter to implement. A political integration formula is needed to combine the demands of unity and diversity. The liberal democracy that is developing at the moment is apparently understood differently by the people in North Sumatra because it is given through a state-centric mechanism. This study uses descriptive qualitative methods. The use of fieldwork with the observation method was carried out. In addition to observation, interviews were also carried out both to the Village Government, Majanggut I, and to the village community. In addition to interviews, various kinds of documentation and literature studies were also used to strengthen the results of this study. The results showed that Majanggut I villagers' understanding of democracy is still limited to the conception of political contestation. Opportunities for locality values to be accommodated in democracy are very open, even though the values of locality in the village are fading away. The Citizenship Politics in Majanggut I Village has not placed citizens as actors of democracy itself. The people of Majanggut I village are still the objects of democracy itself. This indication can be seen from the lack of participation of the village community in the development process in the village and in the process of political development, including in the contestation of village head elections.